Women between Education and Marriage: A Field Study of Married Female Students at Oran University - Miloudi, Fatiha; Gharbi Abdelillah, Radia (Journal of Human Sciences, 2022)
Unlike most studies that attach importance to married women’s work in the public space and its relation to family space, our research focuses on the married student’s daily life in both university space and family space. It aims to illustrate the strategies a female student takes by her multiple roles as a student and a wife. This study reveals the woman as a social actor seeking to practice its individuality to raise her cultural level. This urges the consideration of the social and cultural empowerment of married women in their education rights.